Bactericidal activity of essential oil and hydroalcoholic extract of Eucalyptus globulus leaves (Research, Society and Development, 2020)
The study aimed to evaluate the toxicity, total phenolics and antimicrobial activity using essential oil (OE) and hydroalcoholic extract (EH) of Eucalyptus globulus leaves against pathogenic microorganisms of clinical importance. The HE was prepared using the cold maceration method and the EO was extracted by hydrodistillation at 100°C for 3h. The toxicity assay was performed using the Artemia salina Leach bioassay. For antimicrobial activity, the Disc Diffusion technique was used against the bacteria Escherichia coli and Staphylococcus aureus. The toxicity LC50 obtained for EO was 595.2 mg L-1 and for HE it was 574.18 mg L-1 both classified as nontoxic. Regarding antimicrobial activity, EO presented inhibition halos for S. aureus and E. coli of 15 mm, while HE presented halos of 22 mm for S. aureus and E. coli of 17 mm. EO and HE showed antimicrobial activity and atoxicity, being important parameters to point out the products as a therapeutic alternative, encouraging their potential for application.